Secure blockchain assisted of Medical Things using Identity based Encryption Scheme for High Data Security - D. Baby Sathiya (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Through the use of wireless networks, the Internet of Medical Things (IoMT) facilitates communication between patients and healthcare professionals. Consequently, similar to many other Internet of Things (IoT) devices, IoMT devices do not have adequate security protections. Every time a doctor and patient conduct business, our technology utilises a blockchain to encrypt their sensitive medical information. Additionally, the doctor is able to submit the therapy to the blockchain with the assistance of this method. Every time a doctor and patient conduct business, our technology utilises a blockchain to encrypt their sensitive medical information. Additionally, the doctor is able to submit the therapy to the blockchain with the assistance of this method. The study uses the idea of Identity Based Encryption management with blockchain technology. Users protect themselves from fraud and identity theft with the help of the Identity based Management system’s encryption features. By integrating these technologies, the data storage process can be made more secure and safeguard the privacy of the IoMT. This approach is simply modified to enable search capabilities. Lastly, the efficiency and effectiveness of the proposed schemes is verified by comprehensive performance assessments and security studies